Dismantling the dream factory : gender, German cinema, and the postwar quest for a new film language - Baer, Hester (Film Europa ;, 2009)
The history of postwar German cinema has most often been told as a story of failure, a failure paradoxically epitomized by the remarkable popularity of film throughout the late 1940s and 1950s. Through the analysis of 10 representative films, Hester Baer reassesses this period, looking in particular at how the attempt to "dismantle the dream factory" of Nazi entertainment cinema resulted in a new cinematic language which developed as a result of the changing audience demographic. In an era when female viewers comprised 70 percent of cinema audiences a "women's cinema" emerged, which sought to.